Cathepsin B is involved in the apoptosis intrinsic pathway induced by Bacillus Calmette-Guérin in transitional cancer cell lines - Sandes, Eduardo Omar (2007)
Bacillus Calmette-Guérin (BCG) is the most effective treatment for superficial and in situ transitional bladder cancer. Although the complete mechanisms for its effect are not fully understood yet, both immunological and direct effects on tumor cells have been proposed. It has been proposed that apoptotic tumor cells could be better inducers of immunity than necrotic ones. Thus, apoptosis of bladder cancer cells could contribute to a global response to BCG. Lysosomal hydrolase cathepsin B (CB) is involved in the apoptotic process and has a key role in breast cancer cell programmed death through the activation of a pro-apoptotic protein BID. Truncated BID participates in the mitochondrial apoptotic pathway that involves the activation of pro-caspase 9. The possibility that CB can be involved in apoptosis of TCC line has not been explored yet. Therefore, we analyzed the participation of CB in BCG-induced apoptosis of human and murine TCC lines. Apoptosis was evaluated by a morphologic assay and CB activity by a substrate-specific colorimetric method. Expression of CB, BID and pro-caspase 9 was determined by Western blotting. BCG induced apoptosis of murine (MBT2, MB49) and human (T24) TCC lines. An increase in both CB activity and protein was also observed. The apoptosis of T24 and MB49 cell lines was mediated by activation of pro-caspase 9 and BID, both proteins are involved in mitochondrial apoptosis. Apoptosis and activation of pro-caspase 9 and BID were inhibited by CA-074Me (CA), a cell permeable CB inhibitor. Thus, CB is involved in BCG-induced apoptosis of TCC lines, using at least in part the mitochondrial pathway.